Uncaptured: The CCUS Boom, Environmental Justice, and Cancer Alley - Devin A. Lowell (Washington University Journal of Law and Policy, 2024)
This article exposes the environmental justice implications of industrialization-as-climate-mitigation strategies by focusing on their effects on minority communities in south Louisiana. Political and economic forces at the federal and state levels are advocating for increased development of carbon capture utilization and storage systems that will likely retrench Louisiana’s toxic fossil fuel infrastructure. Though these projects increase pollution, they leverage industrial development subsidies or under the guise of environmental justice efforts. But, a greater harm is at play: history shows that the air and water pollution byproducts of these developments are distributed in Louisiana’s minority communities, and there is intention to end these unfair and harmful government supported practice. This essay argues that even if new environmental technology works as intended, new carbon capture systems will in fact increase the burden of environmental harm borne by minority communities while corporations reap large tax benefits. This paper provides two solutions that policymakers should consider address the broader environmental justice implications of new industries and systems and to fulfill promises made by the Biden administration in its environmental justice commitments. First, legislatures must rethink the 45Q tax credit and related subsidies so that they cannot be manipulated to harm the environment or minority communities under the guise of environmental justice. Second, environmental justice policies must be implemented within permitting agencies such that consideration is given to the relative environmental justice burdens created by permit holders who produce hazardous waste and pollution and to deny permits on the basis that their actions will disproportionately burden racial minorities or low-income populations.
Keywords: EnvironmentalJustice; IndustrializationImpacts; CarbonCapture; PollutionBurden; MinorityCommunities